2022
DOI: 10.1371/journal.pgph.0001046
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depressive symptoms among home isolated patients with COVID-19: A cross-sectional study from Province One, Nepal

Abstract: Home isolated patients infected with COVID-19 might be at increased risk of developing mental health problems. The study aimed to identify the prevalence and factors associated with anxiety and depression among COVID-19 home isolated patients in Province One, Nepal. This was a cross-sectional study conducted between February 17, 2021, to April 9, 2021. A total of 372 home isolated patients from Province One were phone interviewed in the study. Anxiety and depression were measured using a 14-items Hospital Anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(38 reference statements)
2
0
0
Order By: Relevance
“…We found that the female sex was significantly associated with an increased risk of probable depression, and similar findings have been reported in several other studies (15,21). Previous studies have reported an association between depression and having a family member diagnosed with COVID-19 but this was not observed among our participants (17,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that the female sex was significantly associated with an increased risk of probable depression, and similar findings have been reported in several other studies (15,21). Previous studies have reported an association between depression and having a family member diagnosed with COVID-19 but this was not observed among our participants (17,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 89%
“…We found a substantial prevalence of clinically significant depressive (18.6%) and anxiety (11.2%) symptoms. The prevalence of depressive symptoms was similar to that reported in studies among COVID-19 infected individuals in Nepal (26.3%) and China (14.2%), however, some other studies have reported higher values (2,(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 87%